Review of Sophisticated for Thermal Management Systems in Battery Cooling - Majeed, Asaad S.; Salih, Salah M.; Kadhum, Mahdi Hatf (Basrah Journal for Engineering Sciences, 2025)
The transition to electric vehicles (EVs) is a crucial step towards mitigating climate change and addressing the global energy crisis. The increasing use of lithium-ion batteries in EVs is attributed to their superior power density and efficiency. However, ensuring optimal battery performance and safety necessitates effective thermal management due to the significant heat generated during operation. Current cooling systems face challenges in maintaining the desired temperature range and uniformity. This paper reviews the state-of-the-art techniques in battery thermal management, focusing on phase change material (PCM) cooling and different cooling methods. This study, in accordance with its developments, compares the advantages and limitations of various cooling methods as potential solutions for next-generation EVs. It highlights the potential of method cooling, which, while promising, needs further research to establish its commercial viability and aims to guide future advancements in battery thermal management for next-generation EVs. Under both typical and extreme usage scenarios, direct cooling may enhance the necessary battery performance and serve as an innovative method for managing the temperature of electric vehicle batteries. The primary challenge of this technique lies in its suitability for commercial application. This article is organized to cover the thermal properties of lithium-ion batteries, the main issues associated with lithium-ion battery heat, a discussion of reversible and irreversible heat generation and their effects on battery performance, as well as strategies for preventing and mitigating thermal runaway in battery systems. Finally, it summarizes the key recommendations for future research on battery thermal management.